Atividade antimicrobiana in vitro de extratos hidroetanólicos de Astronium sp incorporados ou não em sistemas nanoestruturados - Bonifácio, Bruna Vidal [UNESP] (2014)
Herbal medicines have shown amazing results for the treatment of chronic diseases, especially the ones of the digestive tract (gastric and duodenal ulcers, ulcerative colitis and Crohn's disease), diabetes and cancer. The National Policy of Medicinal Plants and Herbal Medicines (Ministry of Health) proposes the study of several plant species, including plants containing the genus Astronium (Anacardiaceae) that includes species such as A. fraxinifolium, A. graveolens and A. urundeuva, which comprise anti-inflammatory, anti-ulcerogenic, healing and antimicrobial properties. In this context, the inclusion of technology in the improvement of medicinal plants should be encouraged since the strategy to incorporate plant extracts in nanostructured systems has optimized their properties. The antimicrobial activity of the extracts, which were incorporated or not into nanostructured systems, was evaluated by microdilution technique for the microorganisms Escherichia coli (ATCC 25922), Staphylococcus aureus (ATCC 25923), Salmonella setubal (ATCC 19196), Helicobacter pylori (ATCC 43504) and Candida albicans (ATCC 18804). The plant extracts were tested at concentrations from 1000 to 7.81 μg/mL, and the following medications were used to check in order to see if they will work with each type of microorganisms: amoxicillin (100 μg/mL) for H. pylori; ampicillin (50 μg/mL) for the other bacteria, amphotericin B (32 μg/mL) and fluconazole (256 μg/mL) for C. albicans. After the incubation at 37 ºC/72 hours under microaerophilic condition for H. pylori; 37 ºC/24 hours for the other bacteria and 37 °C/48 hours for the yeast, spectrophotometric and visual readings were performed, with the developers 0.01% resazurin (bacteria) and 2% 2,3,5-triphenyltetrazolium chloride in order to determine the minimum inhibitory concentration (MIC). The incorporation was prepared into a nanostructured system comprising 10% oil phase (cholesterol), 10% surfactant ...